1983
DOI: 10.1177/002224378302000103
|View full text |Cite
|
Sign up to set email alerts
|

Selected Determinants of Consumer Satisfaction and Complaint Reports

Abstract: Data obtained from 375 members of a consumer panel in a two-phase study of consumer experiences with automobile repairs and services were used to examine the antecedents and consequences of consumer satisfaction. The results support previous findings that expectations and disconfirmation are plausible determinants of satisfaction, and suggest that complaint activity may be included in satisfaction/dissatisfaction research as suggested by earlier descriptions of consumer complaining behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 432 publications
(87 citation statements)
references
References 18 publications
3
81
0
3
Order By: Relevance
“…This hypothesis is based on past research, which confirmed that emotional reactions following a negative experience with the service provider (eg anger) are associated with attribution of control to the service provider and are also negatively related to clients' evaluation of service and overall evaluation of satisfaction with the service (Bitner, 1990;Folkes, Koletsky and Graham, 1987;Taylor, 1994 Figure 1: Conceptual framework and hypotheses for studying the effect of public self-consciousness disposition on reactions to waiting waiting experience and behavioural intentions, the more subjects evaluate the waiting experience positively, the more favourable their behavioural intentions will be (H 8 ). This hypothesis supports the services marketing literature, in which the influence of satisfaction on future purchase intentions and the content of word-ofmouth communications are recognised (Bearden and Teel, 1983;Cronin and Taylor, 1992).…”
Section: Introductionsupporting
confidence: 85%
“…This hypothesis is based on past research, which confirmed that emotional reactions following a negative experience with the service provider (eg anger) are associated with attribution of control to the service provider and are also negatively related to clients' evaluation of service and overall evaluation of satisfaction with the service (Bitner, 1990;Folkes, Koletsky and Graham, 1987;Taylor, 1994 Figure 1: Conceptual framework and hypotheses for studying the effect of public self-consciousness disposition on reactions to waiting waiting experience and behavioural intentions, the more subjects evaluate the waiting experience positively, the more favourable their behavioural intentions will be (H 8 ). This hypothesis supports the services marketing literature, in which the influence of satisfaction on future purchase intentions and the content of word-ofmouth communications are recognised (Bearden and Teel, 1983;Cronin and Taylor, 1992).…”
Section: Introductionsupporting
confidence: 85%
“…Both these two sets of measures were adapted from Rodriguez Mosquera et al (2010). Consumer satisfaction for the consumption situation was measured with one item commonly used to assess satisfaction (Bearden and Teel, 1983;Westbrook and Oliver, 1991), measuring overall satisfaction (7-point response scale).Additional measures used were: the Dispositional Envy Scale (DES -Smith et al, 1999) -8 items (alpha = .86); and Materialism (Richins, 2004) -15 items (alpha = .93).…”
Section: Methodsmentioning
confidence: 99%
“…In this study consumer satisfaction for the consumption situation was measured with two items to overcome the potential limitations associated with the use of a single item. The items were "I am satisfied with the consumption experience for which I was envied" and "Ultimately, I feel satisfied with this consumption experience" (adapted from Bearden and Teel, 1983;Westbrook and Oliver, 1991). We also measured need for status of respondents as a control with the 5-item Status Consumption Scale (Eastman et al 1999).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Several past studies posit service quality as a significant factor contributing to not only higher customer satisfaction (e.g., Bearden and Teel, 1983;Spreng and Mackoy, 1998;Beerli et al, 2004;Jain, 2008;Oyeniyi and Abiodun, 2008;Naeem and Saif, 2009;Awan et al, 2011), but also reduced operating costs, improved sales and profits (e.g., Boulding et al, 1993;Taylor and Baker, 1994;Zeithaml, 1996), greater customer loyalty (Beerli et al, 2004;Islam and Ali, 2011) and favorable word-ofmouth (WOM) communication (Zeithaml, 1996).…”
Section: Concept Of Service Quality and Its Domain: An Overviewmentioning
confidence: 99%